Analisis Implementasi E Budgeting Dalam Mendukung Transparansi Pada Pemerintah Kota Surakarta - ADE FIRLI JULIANTY; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2020)
Decentralization provides broad opportunities for local governments to develop regional potential according to regional needs and priorities. Technological advances have created a model of public services that are carried out through electronic systems, and public monitoring of public policies demands that the government be more transparent and accountable.This study describes implementation of E budgeting in the city government of Surakarta and transparency of government towards the public. This research uses descriptive qualitative research methods with data collection techniques through interviews, documentation and literature review conducted on related informants.The city govenrment of Surakarta utilizes information technology to demonstrate transparency and accountability from the local government to the people of the city of Surakarta. The realization of transparency can be seen from the government’s efforts to publish the implementation of the planning, budgeting and program activities of the city government of Surakarta.Implementation of E budgeting in the city government of Surakarta is quite good. This study describes the implementation of E budgeting and transparency. It is hoped that the next research will further deepen research on E budeting in the city government of Surakarta.